THE SIGNIFICANCE OF A ARTWORK IN THE FORMATION OF LEARNING SKILLS (Academia Science Repository, 2023)
The article describes the issues of developing oral and coherent speech, increasing vocabulary, teaching to read correctly and expressively, as well as the formation of reading and speech culture and the ability to think independently.